An Individual‐Differences Framework for Comparing Nonnative With Native Speakers: Perspectives From BLC Theory. (8th September 2018) - Hulstijn, Jan H.
Abstract: This article proposes basic (shared) and extended (nonshared) language cognition in native speakers as a function of two types of extralinguistic attributes: (a) degree of being multilingual and (b) variables related to amount and type of literacy experiences (e.g., level of education). This approach may throw new light on the question of whether bilinguals can attain complete or native proficiency in two (or more) languages and the question of whether both early and late second language (L2) learners can attain native levels of L2 proficiency. An adequate language acquisition theory should explain why some structures are and some other structures are not comprehended and produced by all native speakers and also describe the acquisition over time (development) of lexical‐grammatical structures comprehended or produced by all native speakers or only by some. It is argued that usage‐based linguistics stands a better chance of accomplishing this task than generative linguistics.